Atangana-Seda numerical scheme apply to nonlinear circuit problems - Badr Saad T. Alkahtani; Sara Salem Alzaid (Alexandria Engineering Journal, 2020)
Based on the Newton polynomial which is accurate than the Lagrange polynomial, a new numerical scheme was introduced very recently by Atangana and Seda. Their method consisted in reverting a Cauchy problem into a Volterra type and then provide an approximation of the considered nonlinear function using the Newton polynomial. Without any doubt, this method is more efficient and accurate than the well-known Adams-Bashforth, which is based on Lagrange polynomial. In this work, we apply such numerical scheme to some nonlinear circuit problems.